A potentially new evaluation method to visualize rest-activity rhythm based on inpatient activity amount - Yuki NAKAGAWA; Kaoru YAMANO; Kazue NODA; Hiroaki NARITOMI; Hiroshi FURUKAWA (Japanese Journal of Health Promotion, 2023)
[Abstract] [BACKGROUND]: A 24 -hour periodic regression analysis is often conducted for the humans' rest-activity rhythm indexed by activity amount. However, this analysis cannot be said to accurately capture the rest-activity rhythm of inpatients. [OBJECTIVE]: We preliminarily developed a new evaluation method to accurately visualize the complex 24-h rest-activity rhythms of inpatient life. [METHODS]: Physical activity of one male inpatient was measured. The periodic regression analysis in a 24- or 12-h cycle as well as a synthetic 24- and 12-h cycle were applied to the activity amount data. [RESULTS]: A periodic regression analysis with only a 24-h period resulted in y = 1.19352 + 0.115537 * cos(15・t-183.662). The multiple contribution ratio (R2) was 0.76. A periodic regression analysis with only a 12-h period resulted in y = 1.19352 + 0.0444696 * cos(30・t-273.522). The R2 was 0.11. The results of the synthetic periodic regression curve combining the 24- and 12-h periodic components were y = 1.19352 + 0.115537 * cos(15・t-183.662)+ 0.0444696 * cos(30・t-273.522). The R2 was 0.87. The synthetic periodic regression curves were able to capture the subject's rest-activity rhythms more accurately. [CONCLUSION]: The synthetic periodic regression analysis on the activity amount was able to capture more accurately the rest-activity rhythm of the subject. In the future, it is necessary to examine the reliability and validity of the rest-activity rhythm based on synthetic periodic regression analysis by increasing the number of subjects.